Development and Application of Ionospheric Detection Technology. Issue 1 (1st December 2022) - Sun, Haiyang; Xu, Liren; Wang, Shengguo; Wu, Yiyun
Abstract: Aiming at the needs of ionospheric detection and application development, this paper mainly introduced the current development and analyzed the advantages and disadvantages of ionospheric detection technology from ground-based and space-based instruments. Meanwhile, the hot topics of ionospheric application were introduced from the three aspects of ionospheric irregularity, earthquake-ionospheric effect, and ionospheric heating, respectively. Finally, the development trend of ionospheric detection technology and its application were discussed from five aspects, and some suggestions for the future comprehensive research fields of ionospheric detection technology in China were also given.